Effects of seam and surface texture on tennis balls aerodynamics - Djamovski, V.; Pateras, J.; Chowdhury, H.; Alam, F.; Steiner, T. (Procedia Engineering, 2012)
Currently, serving becomes a dominant factor in tennis tournament as the ball travels faster and sometimes the returning player and spectators are unable to follow the track of the ball. As a result, the game becomes boring causing the spectator to lose passion for the game. The reduced speed of the ball can make the game more enjoyable. The understanding of aerodynamic behaviour of tennis balls is important in helping to design and develop a ball that can slow down the game. The complex surface texture of a tennis ball may affect its aerodynamic behaviour as well. As limited information on aerodynamic behaviour of contemporary tennis balls are available, a study was undertaken to investigate the effects of seam and surface texture of a range of commercially manufactured tennis balls. The drag coefficients were analysed and compared. The surface texture and seam orientation showed a noticeable variation in drag coefficients among these balls.